Manajemen Kaderisasi Guru Al-Qur’an untuk Meningkatkan Mutu Pendidikan di Pondok Pesantren Al-Urwatul Wutsqo Bulurejo Diwek Jombang - Moh. Zahiq (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2018)
This study is done in al Urwatul Wutsqo boarding school, and focusing on three aspects, such as cadres forming quality; cadres forming of al Qur’an teacher to increase education quality; and the problems occurred in conducting cadres forming in al Urwatul Wutsqo. The research results are: 1. the cadres forming quality are in the field of a) government support; b) effective leader in managing; c) professional teacher; d) the relevance curriculum; e) graduate with certain quality; f) good culture organization and climate; g) community and parents ‘support. 2. The cadres forming management of al Qur’an teacher to increase education quality are in the field of a) implementation of cadres forming started from the first time the students stay at the boarding house; b) it conducted at diniyah; the graduates are given a card as proof that they have been graduated; practicing of teaching in the institution nearby; 3. The obstacle factors are: a) less of human resources; b) less of cadres forming; c) teachers; and d) the fluctuate system.